Dynamic characterisation of interlaminar fracture toughness in carbon fibre epoxy composite laminates. (November 2019) - Riezzo, M.A.; Simmons, M.; Russell, B.; Sket, F.; Martínez, V.; González, C.
Abstract: In this work, the rate dependence of mode I interlaminar fracture toughness for two different materials systems, IM7/8552 and IM7/M91, both unidirectional UD carbon-fibre epoxy composite laminates have been examined over a wide range of loading rates from 0.5 mm/min up to 2000 mm/s at room temperature. Quasi-static fracture tests were performed using a DCB (double-cantilever beam) method with a screw-driven testing machine, while the dynamic tests were carried out using a WIF (wedge-insert fracture) specimen loaded dynamically in a hydraulic system. For performing the tests at high displacement rates, a special setup was designed and manufactured which allowed the insertion of the wedge within the DCB specimens at different cross-head displacement rates. The experimental technique used a pair of strain gauges attached to the bending surface of one of the arms of the cantilever beams and far from the initial crack tip. The peak values of the recorded strain were used to determine the fracture toughness under dynamic conditions through use of the compliance calibration method. A finite element model was developed to check the consistency of the measurements and validate the data reduction method used. The results exhibited rate insensitive behaviour in the case of the IM7/8552 laminates while IM7/M91 showed the contrary behaviour with maximum peak at 500 mm/s of displacement rate, with a toughness increase of ≈ 95 % with respect to the quasi-static conditions.